2015
DOI: 10.1007/s10140-015-1338-1
|View full text |Cite|
|
Sign up to set email alerts
|

Non-fecalith-induced appendicitis: etiology, imaging, and pathology

Abstract: This study aims to document the imaging and pathology findings in non-fecalith-induced appendicitis. We reviewed the imaging and pathologic findings in 40 patients with histologically proven purulent appendicitis seen over a 2-year period. Findings documented were (1) total appendiceal involvement, (2) predominant appendiceal tip involvement, (3) presence of a fecalith, and (4) presence of lymphoid hyperplasia. There were a total of 40 patients, 28 males and 12 females. The age range was 2-18 years with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Five ICSRs mention appendicoliths, as a reported term or in the case narrative, and all reports of appendicolith with COVID-19 vaccine are in this case series. Lymphoid hyperplasia has also been identified as an important cause of appendicitis [2] , [24] as it can cause obstruction and lead to appendicitis [16] . Appendicitis has presented simultaneously in different underlying causes of lymphadenopathy and lymphoid hyperplasia, such as viral infection, leukemia and lymphoma [4] , [18] , [24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five ICSRs mention appendicoliths, as a reported term or in the case narrative, and all reports of appendicolith with COVID-19 vaccine are in this case series. Lymphoid hyperplasia has also been identified as an important cause of appendicitis [2] , [24] as it can cause obstruction and lead to appendicitis [16] . Appendicitis has presented simultaneously in different underlying causes of lymphadenopathy and lymphoid hyperplasia, such as viral infection, leukemia and lymphoma [4] , [18] , [24] .…”
mentioning
confidence: 99%
“…Lymphoid hyperplasia has also been identified as an important cause of appendicitis [2] , [24] as it can cause obstruction and lead to appendicitis [16] . Appendicitis has presented simultaneously in different underlying causes of lymphadenopathy and lymphoid hyperplasia, such as viral infection, leukemia and lymphoma [4] , [18] , [24] . Lymphadenopathy is listed as a side-effect of the vaccines.…”
mentioning
confidence: 99%
“…Our data do not prove that obstruction leads to antibiotic failure; further analyses will be needed to address this issue. Although obstruction is not a consistent requirement for the initial development of appendicitis, earlier authors have noted that antibiotics may be insufficient when luminal obstruction is present in established appendicitis; thus, the mechanisms underlying the progression of established appendicitis may differ from those contributing to the initial onset of appendicitis. We addressed only patients with histopathologically proven disease because the distinction between complicated and uncomplicated disease is possible only with surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Appendicitis with fecalith(s) is often encountered in clinical practice. The ratio of appendicitis cases with fecalith has been reported in different studies [1][2][3][4], some of which have reported an association between the appendix and fecalith formation, and that fecalith formation is associated with perforation in cases of acute appendicitis and the failure of conservative treatment [5][6][7]. Others have demonstrated that fecaliths do not influence gangrenous or perforated appendicitis [3].…”
Section: Introductionmentioning
confidence: 98%